RESPON PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS AKIBAT PEMBERIAN BOKASHI DAN ZPT AIR KELAPA - Sri Handayani Cut Mulia Sari (Universitas Jabal Ghafur, 2020)
This study aims to determine the response of growth and production of sweet corn plants due to the provision of bokashi and coconut water ZPT and the presence or absence of interaction between the two factors tested. This research was conducted in experimental garden of Faculty of Agriculture of Jabal Ghafur University Sigli from June 03 until August 08, 2017. This research using Randomized Block Design (RAK) of factorial pattern consists of two factors, namely bokashi and ZPT Coconut Water. Each treatment was repeated 3 times, so there were 9 treatment combinations and 27 experimental units. The Bokashi (B) factor consists of: 3.6 kg per plot (B1), 6 kg per plot (B2), 8.4 kg per plot) (B3) and Coconut Water ZPT factor (A) consists of: 500ml / liter water per plot (A1), 1000ml / liter of water per plot (A2) and 1500 ml / liter of water per plot (V3). The results showed that, Bokashi and ZPT Coconut Water had no significant effect on all parameters observed and no interaction between them. Keywords: Bokashi, ZPT Coconut Water and Sweet Corn